The exceptionally efficient quorum quenching enzyme LrsL suppresses Pseudomonas aeruginosa biofilm production - Rehman, Zahid Ur; Momin, Afaque A.; Aldehaiman, Abdullah; Irum, Tayyaba; Grünberg, Raik; Arold, Stefan T. (Frontiers in Microbiology, 2022)
Quorum quenching (QQ) is the enzymatic degradation of molecules used by bacteria for synchronizing their behavior within communities. QQ has attracted wide attention due to its potential to inhibit biofilm formation and suppress the production of virulence factors. Through its capacity to limit biofouling and infections, QQ has applications in water treatment, aquaculture, and healthcare. Several different QQ enzymes have been described, however, they often lack the high stability and catalytic efficiency required for industrial applications. Previously, we identified genes from genome sequences of Red Sea sediment bacteria encoding potential QQ enzymes. In this study, we report that one of them, named LrsL, is a metallo--lactamase superfamily QQ enzyme with outstanding catalytic features. X-ray crystallography shows that LrsL is a zinc-binding dimer. LrsL has an unusually hydrophobic substrate binding pocket that can accommodate a broad range of acyl-homoserine lactones (AHLs) with exceptionally high affinity. In vitro, LrsL achieves the highest catalytic efficiency reported thus far for any QQ enzyme with a Kcat/KM of 3 x 107. LrsL effectively inhibited Pseudomonas aeruginosa biofilm formation without affecting bacterial growth. Furthermore, LrsL suppressed the production of exopolysaccharides required for biofilm production. These features, and its capacity to regain its function after prolonged heat denaturation, identify LrsL as a robust and unusually efficient QQ enzyme for clinical and industrial applications.